Year-End Spending Fever: a Seasonal Phenomenon in the State of Chile - Arancibia Bustos, Ricardo (Revista del CLAD Reforma y Democracia, 2020)
The quality of public spending becomes more relevant in times of fiscal prudence. The pressure of public institutions to execute economic resources before the end of the year actually generates high spending rates in the last quarter and entails strong operating inefficiencies. This paper aims to demonstrate that this phenomenon has a seasonal and structural character within the government departments and its presence is transversal to different political cycles. Furthermore, international evidence and domestic reality indicate that the modernization of the State has serious challenges regarding tax saving, interannual budgetary flexibility and greater transparency of open data to reduce the control barriers of civil society.
Keywords: Public Expenditure; Public Expenditure Rationalization; Expenditures Administration; Budget; Quality; Chile